2019
DOI: 10.1159/000500315
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor-Associated Macrophages in Leukemia

Abstract: In addition to intrinsic factors, leukemia cell growth is influenced by the surrounding nonhematopoietic cells in the leukemic microenvironment, including fibroblasts, mesenchymal stem cells, vascular cells, and various immune cells. Despite the fact that macrophages are an important component of human innate immunity, tumor-associated macrophages (TAMs) have long been considered as an accomplice promoting tumor growth and metastasis. TAMs are activated by an abnormal malignant microenvironment, polarizing int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Additionally, tumor cells in the TME are able to control the immune response by increasing the amount of myeloid-derived suppressor cells, tumor-associated neutrophils (TANs), dendritic cells, and tumor-associated macrophages (TAMs) [ 111 ]. TAMs, like CAFs, participate in tumorigenesis by promoting genetic instability and tumor growth, nurturing CSCs, paving the way to metastasis and suppressing the protective adaptive immunity [ 122 , 123 ]. TAMs can perform different functions by differentiating into different subtypes through a process called polarization, which involves bidirectional interaction between the tumor microenvironment and macrophages.…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, tumor cells in the TME are able to control the immune response by increasing the amount of myeloid-derived suppressor cells, tumor-associated neutrophils (TANs), dendritic cells, and tumor-associated macrophages (TAMs) [ 111 ]. TAMs, like CAFs, participate in tumorigenesis by promoting genetic instability and tumor growth, nurturing CSCs, paving the way to metastasis and suppressing the protective adaptive immunity [ 122 , 123 ]. TAMs can perform different functions by differentiating into different subtypes through a process called polarization, which involves bidirectional interaction between the tumor microenvironment and macrophages.…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
“…TAMs can perform different functions by differentiating into different subtypes through a process called polarization, which involves bidirectional interaction between the tumor microenvironment and macrophages. These TAM subtypes are classically activated macrophages (M1) and alternatively activated macrophages (M2) [ 122 ]. M1 macrophages have antitumor effects, produce pro-inflammatory factors, and participate in the immune defense against external pathogens.…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…TAMs promote immune suppression angiogenesis, and metastasis in cancers via the release of chemokines, cytokines, matrix metalloproteases and growth factors. Enhanced infiltration of TAM is related to a poor prognosis in NSCLC 12,13 . Earlier research has revealed that STAT‐3, NF‐κB (nuclear factor‐κB) and hypoxia‐inducible factor‐1 signalling pathways play a role in recruitment and polarization of TAMs 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced infiltration of TAM is related to a poor prognosis in NSCLC. 12,13 Earlier research has revealed that STAT-3, NF-κB (nuclear factor-κB) and hypoxia-inducible factor-1 signalling pathways play a role in recruitment and polarization of TAMs. 14,15 However, the process involved in TAMs infiltration of the NSCLC cells has not been well elucidated.…”
mentioning
confidence: 99%